2020
DOI: 10.1136/bmjoq-2019-000680
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary, patient-centred approach to improving compliance with venous thromboembolism (VTE) prophylaxis in a district general hospital

Abstract: Hospital-acquired venous thromboembolism (VTE) accounts for an estimated 25 000 preventable deaths per annum in the UK and is associated with significant healthcare costs. The National Institute for Health and Care Excellence guidelines on the prevention of VTE in hospitalised patients highlight the clinical and cost-effectiveness of VTE prevention strategies. A multidisciplinary quality improvement team (MD QIT) based in a district general hospital sought to improve compliance with VTE prophylaxis prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Similar to the studies by Kaufman et al (2020) and Nana et al (2020), the sticker prompts appeared to increase clinicians' rates of enquiry about the sticker subject with the patient. A significant theme was the idea that the stickers prompted clinicians to spend more time on conversations around patients' cultural needs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the studies by Kaufman et al (2020) and Nana et al (2020), the sticker prompts appeared to increase clinicians' rates of enquiry about the sticker subject with the patient. A significant theme was the idea that the stickers prompted clinicians to spend more time on conversations around patients' cultural needs.…”
Section: Discussionsupporting
confidence: 74%
“…For example, Kaufman et al (2020) utilised a sticker prompt as part of a package to increase midwife antenatal vaccine discussions and improve maternal and childhood vaccine uptake. Simple clinical reminders have been shown to increase physician awareness and compliance with best practice in areas such as venous thromboembolism prophylaxis (Nana et al, 2020), antimicrobial prophylaxis (Hill et al, 2021) and managing dehydration in the elderly (Bhatti et al, 2017). The fact that a visual prompt was effective in this diverse range of health contexts suggested that it might be an effective way to remind practitioners about patient ethnicity in situ and also to facilitate broader discussions about culturally responsive care given in the paediatric ward environment.…”
Section: Introductionmentioning
confidence: 99%
“…The expectations are that the NICE guidelines should focus on all hospitalised patients and provide patientcentred care across different healthcare specialities [14]. Therefore, adherence to NICE guidelines should allow enhanced VTE prophylaxis administration and reduced DVT incidences [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the benefit of a paperless system, where real-time prescribing prompts can be given which account for clinical information, as opposed to static prompts, and where analysis includes all records overs a prolonged period. Some quality improvement papers in this field are based on standard audit procedures, where only a proportion of records are reviewed over a short period, leading to a significant risk of bias and making it unclear whether improvements were maintained [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%